Impact of monetary incentives on teacher decisions to leave and choose schools: Evidence from a policy reform in Sao Paulo - Gregory Elacqua; Mateus Rodrigues; Leonardo Rosa (Inter-American Development Bank (IDB), 2025)
Teacher turnover is a major challenge for human resource management in schools, adversely affecting student learning. We examine the impact of a monetary incentive program introduced in 2022 in the city of Sao Paulo, Brazil, which aims to reduce teacher turnover by allocating wage premiums ranging from 5% to 25% of base salary based on schools turnover levels. Our results show a significant reduction in turnover: an average decrease of 18% across all schools, with an even more pronounced 30% reduction in schools offering higher incentives. Notably, the program also attracted new teachers to these higher-incentive schools. An analysis of teacher preferences similarly reveals a shift towards schools offering greater wage premiums. Furthermore, we find that schools offering high incentives experienced significant improvements in student test scores, with gains of 0.3-0.6 standard deviations in standardized assessments. The findings demonstrate the effectiveness of monetary incentives in mitigating teacher turnover and improving educational outcomes, providing evidence-based guidance for policymakers developing teacher retention strategies.
Keywords: I21; J45; J63; M52; 330; teachers; financial incentives; teacher shortage; teacher sorting; turnover rates; disadvantaged schools; Brazil